The rationale behind updates to ambient ozone guidelines and standards - Xue, Kaibing; Zhang, Xin (Frontiers in Public Health, 2023)
Although air quality has gradually improved in recent years, as shown by the decrease in PM 2.5 concentration, the problem of rising ambient ozone has become increasingly serious. To reduce hazards of human health and environmental welfare exposure to ozone, scientists and government regulators have developed the ozone guidelines and standards. These answer the questions that which levels of exposure are hazardous to human health and the environment, and how can ambient ozone exposure be guaranteed, respectively. So what are the basis for the ozone guidelines and standards? This paper detailedly reviews the process of revising ozone guidelines or standards in WHO and U.S. EPA and attempts to explore and analyze the scientific basis and empirical methods for updating guidelines and standards, in a view to guide the future revision process and provide directions for further scientific research. We found many epidemiological and toxicological studies and exposure-response relationships provided strong support for developing and revising the ozone guidelines. When setting the standards, the ozone exposure in the region has been effectively considered, and the economic costs and the health as well as indirect economic benefits of standard compliance were reasonably estimated. Accordingly, the epidemiological and toxicological studies and establishment of exposure-response relationships, as well as exposure and risk assessment, and benefit-cost estimate of standards compliance should be strengthened for the further update of guidelines and standards. What's more, with the increasing prominence of combined air pollution led by ozone and PM 2.5 , more joint exposure scientific research related to ozone guidelines and standards should be paid attention to.